BACTERIAL SUSCEPTIBILITY-RESISTANCE LEVELS OF CHRONIC PYELONEPHRITIS PATHOGENS’, DEPENDING ON EXPRESSION OF DIFFERENT TYPES OF PLASMID-MEDIATED RESISTANCE GENES - ChubО.І.; Bilchenko, O.V.; Teslenko, S.V. (Ukrainian Journal of Nephrology and Dialysis, 2017)
The aim of the study is to determine the bacterial susceptibility-resistance levels of uropathogens depending on expression of different types of plasmid-mediated resistance genes. Methods. A cross-sectional study of105 patients with chronic pyelonephritis was carried. Screening for the presence of plasmid-mediated genes was performed by polymerase chain reaction. The antimicrobial susceptibility of isolates was determined by the Kirby Bauer disk diffusion method on Mueller–Hinton agar-containing plates. The size of zone around each antimicrobial disk was interpreted as sensitive, intermediate or resistant. Results. We demonstrated in vitro significant relationship of the resistance to aminopenicillins, cephalosporins and fluoroquinolones with an appearance of plasmid-mediated extended spectrum p-lactamases (ESBLs) types blaCTX-M, blaTEM, blaSHV and fluoroquinolones resistant genes (PMQR), including QnrA, AAC (6’) - Ib-cr, QepA) in bacterial uropathogens. We also demonstrated in vitro significant relationship of the resistance to aminoglycosides with an appearance of plasmid-mediated genes blaCTX-M, QnrA and QepA. Conclusion. Were established in vitro significant relationships of the resistance to antimicrobials with an appearance of plasmid-mediated resistance genes in uropathogens. Were determined the most effective antibiotics against ESBL and PMQR producers. We have established the algorithm of diagnostic of plasmid-mediated resistance genes in uropathogens, isolated from patients with chronic pyelonephritis.